Patient‐individual phenotypes of glioblastoma stem cells are conserved in culture and associate with radioresistance, brain infiltration and patient prognosis. Issue 10 (14th February 2022) - Ganser, Katrin; Eckert, Franziska; Riedel, Andreas; Stransky, Nicolai; Paulsen, Frank; Noell, Susan; Krueger, Marcel; Schittenhelm, Jens; Beck‐Wödl, Stefanie; Zips, Daniel; Ruth, Peter; Huber, Stephan M.; et al.
Abstract: Identification of prognostic or predictive molecular markers in glioblastoma resection specimens may lead to strategies for therapy stratification and personalized treatment planning. Here, we analyzed in primary glioblastoma stem cell (pGSC) cultures the mRNA abundances of seven stem cell (MSI1, Notch1, nestin, Sox2, Oct4, FABP7 and ALDH1A3), and three radioresistance or invasion markers (CXCR4, IKCa and BKCa ). From these abundances, an mRNA signature was deduced which describes the mesenchymal‐to‐proneural expression profile of an individual GSC culture. To assess its functional significance, we associated the GSC mRNA signature with the clonogenic survival after irradiation with 4 Gy and the fibrin matrix invasion of the GSC cells. In addition, we compared the molecular pGSC mRNA signature with the tumor recurrence pattern and the overall survival of the glioblastoma patients from whom the pGSC cultures were derived. As a result, the molecular pGSC mRNA signature correlated positively with the pGSC radioresistance and matrix invasion capability in vitro. Moreover, patients with a mesenchymal (>median) mRNA signature in their pGSC cultures exhibited predominantly a multifocal tumor recurrence and a significantly (univariate log rank test) shorter overall survival than patients with proneural (≤median mRNA signature) pGSCs. The tumors of the latter recurred predominately unifocally. We conclude that our pGSC cultures induce/select those cell subpopulations of the heterogeneous brain tumor that determine disease progression and therapy outcome. In addition, we further postulate a clinically relevant prognostic/predictive value for the 10 mRNAs‐based mesenchymal‐to‐proneural signature of the GSC subpopulations in glioblastoma. Abstract : What's new? Individualized treatment for glioblastoma could help improve survival for this cancer, which generally has a poor prognosis. Here, the authors measured abundances of 10 mRNAs in primary cultures of glioblastoma stem cells (pGSCs) and identified an RNA signature that correlates with radiation resistance and invasiveness. They also found that the mRNA signature correlated with the tumor recurrence pattern and overall survival of the glioblastoma patients that the pGSCs came from. Thus, culturing pGSCs may provide a platform for predicting response to treatment or determining prognosis.